EDUKASI KESEHATAN GIGI DAN MULUT PADA SISWA DI SDK REJENG KECAMATAN LELAK , MANGGARAI - Maria Getrida Simon (Unika Santu Paulus Ruteng, 2024)
Dental health or now referred to as oral health is the well-being of the oral cavity including the teeth and their structures and supporting tissues free from disease, and the mouth and its supporting tissues function optimally, which will cause disease. Statistics show that dental and oral diseases affect almost everyone. (Sriyono, 2011 in Listrianah). For dental and oral health, based on Riskesdas 2018 data, it was recorded that the proportion of dental and oral problems for the 3-4 year age group was 41.1% and the 5-9 year age group was 67.3% and those who received services from dental medical personnel for the age 3-4 years by 4.3% and age group 5-9 years by 14.6%. The proportion of dental and oral health and hygiene care counseling behavior for the 3-4 year age group was 5.4% and the 5-9 year age group was 8.3%. Seeing the existing phenomenon that the dental and oral health of the Indonesian people needs to be improved and paid attention to and generally children entering school age have a risk of dental caries, this condition of dental caries can cause the child to experience chewing power which gradually disappears and digestive disorders, as a result of this there will be less than optimal growth (Sinaga, 2013). This will interfere with learning concentration, frequency of attendance at school and affect appetite and food intake so that it will impact on children's nutritional status (Worotitjan et al, 2013; Permatasari, 2014). This activity was carried out for 2 days, where on the first day there were counseling activities after that they carried out mass tooth brushing and continued on the second day a dental examination was carried out by the medical team from the Lelak Health Center.